Management of the Nuchal Cord at Birth - David JR Hutchon FRCOG (Mashhad University of Medical Sciences, 2013)
Background and aim: Although nuchal cord is a common occurrence at birth, there is little attention to its importance or management at birth, and teaching includes premature clamping and cutting of the cord as the common option.  Although grade 1 evidence is lacking, the optimal management of the nuchal cord,  the Somersault manoeuvre  is not taught or included in any current guidelines. What evidence there is, presented in this review.